2010
DOI: 10.1097/sla.0b013e3181c1aeb8
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Versus Water-Soluble Contrast Swallow in the Detection of Intrathoracic Anastomotic Leak Complicating Esophagogastrectomy (Ivor Lewis)

Abstract: In comparison with CS only, CT at day 7 improves the sensitivity and negative predictive value for diagnosing an anastomotic leak. In case of doubt endoscopy is advisable. This approach provides an accurate assessment of the anastomosis before refeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 15 publications
3
58
0
3
Order By: Relevance
“…Thus, most of the AL in our series (20 of 49; 41%) were diagnosed by CT scan of the chest and abdomen (Fig. 2), in accordance with existing literature [18, 19, 21]. In case of early AL ( n  = 11), 3 (27%) patients were diagnosed by suspicious fluid from the peri-anastomotic drain and did not receive further CT scans before initiating revision surgery ( n  = 2) or stenting ( n  = 1).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Thus, most of the AL in our series (20 of 49; 41%) were diagnosed by CT scan of the chest and abdomen (Fig. 2), in accordance with existing literature [18, 19, 21]. In case of early AL ( n  = 11), 3 (27%) patients were diagnosed by suspicious fluid from the peri-anastomotic drain and did not receive further CT scans before initiating revision surgery ( n  = 2) or stenting ( n  = 1).…”
Section: Discussionsupporting
confidence: 76%
“…In their BestBET study, Jones et al [23] analyzed the data of 1,057 patients to evaluate “the role of routine contrast swallow studies in determining intra-thoracic anastomosis integrity.” Interestingly, the authors suggested “the use of contrast esophagograms as a diagnostic tool in patients for whom the clinical picture suggests a leak.” However, in our opinion and in accordance with Strauss et al [18] and Hogan et al [19] a thoracoabdominal CT scan with oral contrast agent should be performed when AL is clinically suspected to reliably diagnose the AL and further complications (e.g., mediastinitis, abscess, pneumonia etc.). In case of unclear CT results, endoscopy is indicated, as mentioned by some authors [18, 19].…”
Section: Discussionmentioning
confidence: 97%
“…Further examinations should be conducted to confirm or to rule out the leakages. CT with oral radiographic contrast such as Iohexol is a feasible and sensitive way to diagnose anastomotic leakage, and repeated examinations in the suspected cases can increase its sensitivity (9,10). The other optional method is the observing presence of methylene blue in pleural effusion or in pus from the thoracic drainage of the patients with suspected leakages after orally intake of methylene blue (11).…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports regarding the use of endoscopy to observe anastomosis [8,9,10]. Some reports concluded that the sensitivity of endoscopy was higher compared with other examinations or physical symptoms [3].…”
Section: Discussionmentioning
confidence: 99%